Beban Pikiran dan Mahkota yang Gugur: Fenomena Telogen Effluvium pada Mahasiswi Kedokteran - Putri Iftinan Azhar; Etty Farida Mustifah; Joko Susanto (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2025)
Background : Stress is a disease that is often experienced by people in the world. Hair loss is one of the effects of stress which is known to be more susceptible to women. The high burden on medical students can trigger stress which can trigger hair loss. Objective : To determine the relationship between stress levels and the incidence of telogen effluvium in students at the Faculty of Medicine, Muhammadiyah University, Prof. Dr. HAMKA. Method : This research uses a cross-sectional study. Data collection was carried out using the PSS-10 questionnaire instrument and the excessive telogen hair loss questionnaire which had been tested for validity and reliability. A total of 63 samples were taken using the proportional random sampling method. Data were analyzed using the Kolmogorov-Smirnov test via the SPSS version 25 application. Results : Obtained a P value of 0.002 (P ≤ 0.05). Conclusion : There is a significant relationship between stress levels and the incidence of telogen effluvium in students at the Faculty of Medicine, Muhammadiyah University, Prof. Dr. HAMKA. Latar Belakang : Stres merupakan salah satu penyakit yang sering dialami orang di dunia. Kerontokan rambut menjadi salah satu dampak stres yang diketahui lebih rentan terjadi pada perempuan. Tingginya beban pada mahasiswi kedokteran dapat memicu stres yang bisa memicu kerontokan rambut. Tujuan : Mengetahui hubungan antara tingkat stres dengan kejadian telogen effluvium pada mahasiswi Fakultas Kedokteran Universitas Muhammadiyah Prof. Dr. HAMKA. Metode : Penelitian ini menggunakan studi cross-sectional. Pengambilan data dilakukan dengan instrumen kuesioner PSS-10 dan kuesioner kerontokan rambut telogen berlebih yang sudah diuji validitas dan reliabilitasnya. Sebanyak 63 sampel diambil dengan metode proportional random sampling. Data dianalisis menggunakan uji Kolmogorov-Smirnov melalui aplikasi SPSS versi 25. Hasil : Didapatkan nilai P sebesar 0.002 (P ≤ 0,05). Kesimpulan : Terdapat hubungan signifikan antara tingkat stres dengan kejadian telogen effluvium pada mahasiswi Fakultas Kedokteran Universitas Muhammadiyah Prof. Dr. HAMKA